Peran dan Strategi Public Relations Officer (PRO) dalam Mengoptimalkan Layanan Informasi RSUD dr. Zainoel Abidin di Banda Aceh - Syarifah Chairunnisak (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Quality information services in hospitals is an important element in increasing patient satisfaction and the image of the institution. The Public Relations Officer (PRO) plays a strategic role in managing communication between the hospital and the public. This research aims to explore the strategies implemented by PROs in improving the quality of information services at RSUD dr. Zainoel Abidin Banda Aceh. The public relations officer (PRO) strategy used is determining problems, compiling and planning work programs, taking action and communicating as well as evaluating work programs in hospitals and reviewed through strategic planning in the field of Public Relations by Cutlip-Center-Broom. The research method used was descriptive with a qualitative approach between PROs and several hospital employees, patients and patient families. The results of the investigation revealed that the strategies used by PRO RSUDZA and health services ranged from identifying problems, planning, to compiling work programs, such as online registration, electronic pharmacies (e-pharmacies), and community complaint centers. In addition, PRO RSUDZA deployed staff from the Hospital Health Counseling Service (PKRS) to carry out outreach and communication to inform the public about RSUDZA services and the availability of the RSUDZA tabloid newspaper "Lam Haba". PRO RSUDZA evaluates the work program carried out at the hospital. Obstacles faced by PRO RSUDZA include miscommunication and residents' complaints about long queues at registration and drug distribution counters. PRO RSUDZA's efforts aim to carry out all planned work programs to improve the quality of information services at RSUDZA Banda Aceh.